The Impact of Poverty and Insecurity on Sustainable Development in Nigeria - Abga, Maina Mackson; Magaji, Saidu; Gambo, Khalid Zubairu (Kashere Journal of Politics and International Relations, 2023)
Nigeria has all it takes to be great in terms of human and natural resources to develop one of the greatest economies of the world yet most of her citizens lives in poverty; this unpleasant development has made her being rated as one of the poorest nations in the world. This study examines the impact of poverty and insecurity on sustainable development in North- Western Nigeria: a case study of Katsina State from 2015 – 2022; the objective of the study is to identify the causes of poverty and insecurity and their impact on the lives of the citizens. The study adopted primary and secondary sources of data collections using questionnaire which was complemented with the secondary source of data by reading text books, journals, dissertations, research projects, conferences, seminar and workshop papers on poverty and insecurity. Data were presented and analysed using descriptive and inferential statistics which involved the use of descriptive statistics such as frequency distribution, mean and percentage. The findings suggest that the level of poverty in Nigeria is responsible for the insecurity in the country; though poverty is not a sufficient variable in the explanation of the intense nature of insecurity in Nigeria, nonetheless there is a relationship between poverty and insecurity. The study recommends that good governance can guarantee peace and security so government must create a vibrant economy that will provide social, economic and physical infrastructure that will drive industrial growth and development and ensure social security and curb the menace of poverty and insecurity.